A escolarização obrigatória em contextos federativos : um estudo comparativo entre Brasil e Argentina - Brahim, Cybele Barbosa (2016)
The objective of this study is to analyze public policies that guide compulsory schooling in federal contexts of Brazil and Argentina, based on the legal requirements of both countries. There fore, the theme It was addressed in a comparative perspective, using the literature which includes authors such as Araujo (2005, 2010, 2011a), Cury (2000, 2002ª, 2002b, 2007), Rivas (2004, 2007, 2009), Feldfeber (2009, 2011, 2014). Furthermore, it was conducted documentary research, covering the laws of both countries. At the Brazil, we analyzed the Law of Education Guidelines and Base (LDB) 9394/1996; The Law 11.114 / 2005; Law 11.274 / 2006 and the Constitutional Amendment. 59/2009. In relation to Argentina, were analyzed the Federal Law no. 24,195 / 1993 and Law Education (LEN) 26,206 / 2006. The analysis made possible verify the two countries advanced as regards the compulsory enrollment in under the legislation, extended compulsory schooling in Argentina to 13 years and in Brazil for 14 years. We also identified that while in your origin of these States have been trained in social settings, political and disparate economic, and that these factors contributed to evidence educational discrepancies between Brazil and Argentina in the nineties, the which is currently observed is a certain similarity in the educational framework these countries. We attribute this educational homogenization policies implemented in Latin America by educational reforms devised within a neoliberal vision, under the influence of international organizations. Anyway, although we realize that many steps have been taken in the way towards compulsory schooling.